(untitled) (Journal of human and social sciences, 2015)
This study addresses the phenomenon of lexical borrowing in the Arabic language and the influence of other languages such as Persian and Greek throughout history. It discusses the positions of scholars between rejection and acceptance of this phenomenon, reviews the criteria set by linguists to distinguish between Arabized and original words, and touches upon the presence of foreign words in the Holy Quran and the ongoing debate surrounding them.